Hadis-Hadis Lemah dan Palsu - Mohammad Zainul Wafa (INC- Islam Nusantara Center, 2022)
This study aims to reveal the quality of the hadith sanad contained in the book al-Bayān al-Muṣaffa by Asrori Ahmad, because all the hadiths in the book do not contain sanad, mukharrij, or hadith quality. Kiai Asrori Ahmad is a well-known Javanese researcher, especially in Magelang, Central Java. There is no doubt about his knowledge, many of his writings have been widely studied in society, one of which is this book. Therefore, the hadith listed is often used as a reference. In this study, researchers used data collection methods (library search). Data is collected usingTakhrij Hadith, then the results of takhrij are analyzed using Sanad criticism. The source of this study is the book al-Bayān al-Muṣaffa, which contains 49 hadiths, six of which have no sanad. So the writer makes six hadiths as examples of research. The result is that there are 3 weak hadiths and 3 fake hadiths. Penelitian ini bertujuan untuk mengungkap kualitas sanad hadits yang terdapat dalam kitab al-Bayān al-Muṣaffa karya kiai Asrori Ahmad, karena semua hadis dalam kitab tersebut tidak memuat sanad, mukharrij, maupun kualitas hadits. Kiai Asrori Ahmad adalah seorang peneliti Jawa terkenal, khususnya di Magelang, Jawa Tengah. Ilmunya tidak diragukan lagi, banyak tulisannya yang banyak dipelajari di masyarakat, salah satunya buku ini. Oleh karena itu, hadis yang tercantum sering dijadikan rujukan. Dalam penelitian ini, peneliti menggunakan metode pengumpulan data (library search). Data dikumpulkan dengan menggunakan Takhrij Hadits, kemudian hasil takhrij dianalisis dengan menggunakan kritik Sanad. Sumber kajian ini adalah kitab al-Bayān al-Muṣaffa, yang memuat 49 hadits, enam di antaranya tidak memiliki sanad. Maka penulis menjadikan enam hadis sebagai contoh penelitian. Hasilnya adalah terdapat 3 hadis lemah dan 3 hadis palsu.